The Effects of Cryopreserved Human Amniotic Membrane and Platelet-Rich Plasma on Seroma Development after Mastectomy and Axillary Dissection in Rats - Mustafa Özkaraca; Muhammed Gömeç (Düzce Tıp Fakültesi Dergisi, 2022)
Aim: Seroma is one of the most common complications after mastectomy and axillary dissection. It occurs as a result of prolongation of the exudative-inflammatory phase of wound healing. The aim of this study is to evaluate the effects of human amniotic membrane (HAM) and platelet-rich plasma (PRP) on seroma formation. Material and Methods: A total of 24 rats were grouped as control, PRP, and HAM groups. All rats underwent radical mastectomy and axillary lymph node dissection. Saline in the control group, PRP in the second group, and HAM in the third group were applied to the dissection area. The groups were compared in terms of the condition of the surgical field, seroma volume, and histopathological changes. Results: Seroma volume decreased in the PRP group, but not in the HAM group. Lymphocyte, eosinophil, histiocyte, and fibroblast levels were significantly lower both in the PRP and HAM groups compared to the control group. E-cadherin and TGF-β1 immunoreactivities of PRP and HAM groups were higher than in the control group. Conclusion: In this study, it was observed that PRP and cryopreserved HAM increased tissue healing and decreased the inflammatory process. However, although local PRP application significantly reduced seroma formation, it was determined that HAM application did not reduce seroma formation. It was thought that this might be due to the fact that the smooth surface of HAM mechanically prevents the adhesion of the tissues. More beneficial results will be obtained with the modification to be made in the preparation and application of HAM.